Nurses’ Knowledge and Practice Regarding Prevention of Surgical Site Infection at Governmental Hospitals in Wasit City, Iraq 2022 - Amina Hilal Hassan, Daryadokht Masror-Roudsary (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study was aimed at determining nursing knowledge and practices regarding prevention of surgical site infection in governmental hospitals in Wasit city. Methods: This cross-sectional study was conducted with descriptive design to determine knowledge and practice of nurses who work in surgical wards regarding prevention of SSI in governmental hospitals in Wasit City. A sample of 180 surgical nurses participated in the study (100% response rate); convenience sampling method was used in this study. The instrument used for data collection was a questionnaire which is composed of three parts: Demographic characteristics, Nurses’ knowledge questionnaire, and Nurses’ practice questionnaire. Results: The results of current study revealed that (58.3%) of the nurses expressed a poor knowledge regarding SSI as described by low average, which is equivalent to 7.68 (±7.441), and (75.6%) of the nurses expressed an inadequate practice regarding SSI as described by low average, which is equivalent to 36.89 (±13.55). The results show that nurses practices is positively significant correlated with their knowledge (r = 0.216; p = 0.000). Conclusion: Knowledge and practices among nurses working in surgical words in governmental hospitals (both teaching and non-teaching) in Wasit city regarding SSI prevention were found to be low. Being male with high educational level were factors which were significantly associated with knowledge of prevention of SSI. On the other hand, serving for 1–5 years is a factor that was significantly associated with the practice of SSI prevention activities. Therefore, efforts have to be made to update the knowledge of nurses regarding SSI prevention activities. Additionally, hospital administrators ought to motivate highly educated nurses to concentrate on putting their learning into practice.